(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The transition from traditional, in-person real business to virtual transactions has been a significant phenomenon in the business world. This shift from traditional brick-and-mortar business models to virtual transactions is a monumental shift in the business landscape. Real business involves visiting physical storefronts by the customer, which is now being transformed to sitting and ordering with the atmosphere of own convenience and comfort through digital platforms. Although, this dramatic drift to virtual world provides the market with global reach and scalability, lower operational costs, data-driven analytics and insights, it however, cannot ensure consumer’s justification for product or service verification, a trustworthy relationship between seller-buyer, face-to-face interaction, immediate redressal of their grievances and most importantly ’reduced’ risk of fraud. Based on this quick comparative study, we can say that, "Real business is really a business while virtual transactions are a superstitious business system". As we move further, this paper explores the critical differences, advantages, and challenges associated with these two transaction types.